Characterization of vacancy defects in Cu(In,Ga)Se2 by positron annihilation spectroscopy - M. R. M. Elsharkawy; G. S. Kanda; M. V. Yakushev; E. E. Abdel-Hady; D. J. Keeble (AIP Advances, 2016)
The photovoltaic performance of Cu(In1-x,Gax)Se2 (CIGS) materials is commonly assumed to be degraded by the presence of vacancy-related defects. However, experimental identification of specific vacancy defects remains challenging. In this work we report positron lifetime measurements on CIGS crystals with x = 0, and x = 0.05, saturation trapping to two dominant vacancy defect types, in both types of crystal, is observed and found to be independent of temperature between 15–300 K. Atomic superposition method calculations of the positron lifetimes for a range of vacancy defects in CIS and CGS are reported. The calculated lifetimes support the assignment of the first experimental lifetime component to monovacancy or divacancy defects, and the second to trivacancies, or possibly the large In-Se divacancy. Further, the calculated positron parameters obtained here provide evidence that positron annihilation spectroscopy has the capability to identify specific vacancy-related defects in the Cu(In1-x,Gax)Se2 chalcogenides.